2003
DOI: 10.1051/animres:2003032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein source on digestion and growth performance of early-weaned rabbits

Abstract: -Four diets based on different vegetal protein concentrates: soya bean meal 48 (SB48 diet), soya bean protein concentrate (SB61 diet), sunflower meal 36 (SF36 diet) and a combination of soya bean meal 48 and potato protein concentrate (SB48-P77 diet) were formulated for the starter period (25-39 days) in early weaned rabbits (25 days of age). These sources of protein accounted for 30% of the total dietary crude protein (CP) content. All diets were formulated to be isonutritive and to meet or exceed all the ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 9 publications
8
37
0
1
Order By: Relevance
“…The complete substitution of soybean meal by sunflower meal did not affect growth performance (Table 7) as found in other studies (Gutiérrez et al, 2003). Nevertheless, García-Ruiz et al (2006) observed higher daily weight gain and feed intake in rabbits fed diets based on soybean meal rather than sunflower meal, which were associated to a higher mortality ascribed to the higher ileal flux of soybean protein.…”
Section: Health Status and Growth Performancesupporting
confidence: 74%
See 3 more Smart Citations
“…The complete substitution of soybean meal by sunflower meal did not affect growth performance (Table 7) as found in other studies (Gutiérrez et al, 2003). Nevertheless, García-Ruiz et al (2006) observed higher daily weight gain and feed intake in rabbits fed diets based on soybean meal rather than sunflower meal, which were associated to a higher mortality ascribed to the higher ileal flux of soybean protein.…”
Section: Health Status and Growth Performancesupporting
confidence: 74%
“…CP digestibility tended to be lower (P=0.058) in Sun diets than in Soy diets. Other authors (Gutiérrez et al, 2003;García-Ruiz et al, 2006) did not find differences in faecal apparent digestibility in diets based on sunflower meal (36% CP) or soybean meal (46-48% CP), while measuring a higher ileal digestibility of CP and DM in the former than in the latter (Gutiérrez et al, 2003). EE and hemicelluloses were less digested (P<0.001) in Soy diets than in Sun diets, while ADF and soluble fibre resulted more digested in the former ones.…”
Section: Digestibility and Nutritive Value Of Dietsmentioning
confidence: 87%
See 2 more Smart Citations
“…Dietary levels of the most limiting AA (lysine, methionine+cystine and threonine) were higher (by 22, 32 and 7% , respectively) than recommended levels for the overall fattening period , in order to assure a correct growth in the starter phase (from 25 to 39 days of age). In the post-weaning period, an excess of nitrogen flow in the ileum has been proven to increase intestinal disorders in early weaned rabbits (Gutiérrez et al, 2003;Chamorro et al, 2007). The trend in practical formulation in rabbits is to reduce the level of crude protein increasing in parallel that of limiting synthetic AA (lysine, methionine and treonine) to maintain growth responses.…”
Section: Resultsmentioning
confidence: 99%